PENGARUH DESIGN PRODUCT, BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN SKINCARE PADA KARIN BEAUTY GLAMOUR SUKAWATI - Ni Kadek Tara Wahyuni; I Gusti Ayu Imbayani; I Made Surya Prayoga (VALUES, 2023)
The purchase decision is a stage where the consumer has a choice and is ready to make a purchase orexchange between money and a promise to pay for the ownership or use of an item or service. The growth of the Indonesian economy at a macro level has had a positive impact on consumer purchasing decisions. The Covid-19 pandemic has caused many losses to many businesses, but the beauty business sector is one sector that continues to grow and is much needed by all groups, such as the skincare business, where this assessment is certainly influenced by several factors. Several factors that influence purchasing decisions are Product Design, Brand Image and Brand trust, so the authors want to examine these three variables to determine their impact on purchasing decisions. The population of this study were all customers who visited Karin Beauty Glamor Sukawati with an unknown population size. The research sample was selected using the Incidental Sampling method with the sampling technique using the Hair formula. The sample in this study was 95 respondents who had visited Karin Beauty Glamor Sukawati. The analytical tool used to test the hypothesis is multiple linear analysis but before that the researcher first used validity testing and reliability testing. The test results show that Product Design has a positive and significant effect on Skincare Purchasing Decisions at Karin Beauty Glamour Sukawati. Brand Image has a positive and significant effect on Skincare purchasing decisions at Karin Beauty Glamour Sukawati and Brand Trust has a positive and significant effect on Skincare Purchasing Decisions at Karin Beauty Glamour Sukawati.